2018
DOI: 10.1186/s12889-018-6034-0
|View full text |Cite
|
Sign up to set email alerts
|

Indirect costs and public finance consequences of heart failure in Poland, 2012–2015

Abstract: BackgroundAs a consequence of unfavourable epidemiological trends and the development of disease management, the economic aspects of heart failure (HF) have become more and more important. The costs of treatment (direct costs) appear to be the most frequently addressed topic in the economic research on HF; however, less is known about productivity losses (indirect costs) and the public finance burden attributable to the disease. Therefore, the aim of this study was to estimate the indirect costs and public fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…HF is associated with several symptoms (e.g. shortness of breath and fatigue) that impair quality of life and is also associated with high mortality rates, recurrent hospitalizations, and high direct and indirect costs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HF is associated with several symptoms (e.g. shortness of breath and fatigue) that impair quality of life and is also associated with high mortality rates, recurrent hospitalizations, and high direct and indirect costs …”
Section: Introductionmentioning
confidence: 99%
“…shortness of breath and fatigue) that impair quality of life 3 and is also associated with high mortality rates, recurrent hospitalizations, and high direct and indirect costs. [4][5][6] Cognitive impairment (CI) is a common co-morbid condition in patients with HF. 7 Several studies have shown that CI in HF ranges between 20% and 80%, 7,8 and that CI is associated with poor HF outcomes, such as death, hospital readmission, and poor self-care.…”
Section: Introductionmentioning
confidence: 99%
“…The UK’s Centre for Economics and Business Research concluded that the cost of cardiovascular disease in Europe will rise from €100 billion to approximately €120 billion over the next 10 years [7]. Indirect costs of HF also need to be considered, though less explored, as they contribute extensively to the overall burden caused by HF [24]. For example, in Poland, a substantial public finance burden of HF was calculated at €871.9 million in 2012, which increased to €945.3 million in 2015 [24].…”
Section: Necessity For a Paradigm Shift In The Care Of Hfmentioning
confidence: 99%
“…Indirect costs of HF also need to be considered, though less explored, as they contribute extensively to the overall burden caused by HF [24]. For example, in Poland, a substantial public finance burden of HF was calculated at €871.9 million in 2012, which increased to €945.3 million in 2015 [24].…”
Section: Necessity For a Paradigm Shift In The Care Of Hfmentioning
confidence: 99%
“…During the past decades, the collective of health professionals in developed countries has aged, and this tendency is expected to continue [1,2,3,4]. Soon, the higher prevalence of occupational diseases and work-related health conditions among these workers may reduce their participation in employment, decrease their performance [5,6], and, at the same time, increase their personal health care expenditure and the public health expenditure [7]. Accordingly, the study of health behavior in the face of retirement in this collective is of special interest.…”
Section: Introductionmentioning
confidence: 99%